Exploring mechanisms of change in schema therapy for chronic depression. (March 2018) - Renner, Fritz; DeRubeis, Robert; Arntz, Arnoud; Peeters, Frenk; Lobbestael, Jill; Huibers, Marcus J.H.
Abstract: Background and objectives: The underlying mechanisms of symptom change in schema therapy (ST) for chronic major depressive disorder (cMDD) have not been studied. The aim of this study was to explore the impact of two potentially important mechanisms of symptom change, maladaptive schemas (proxied by negative idiosyncratic core-beliefs) and the therapeutic alliance. Methods: We drew data from a single-case series of ST for cMDD. Patients with cMDD (N = 20) received on average 78 repeated weekly assessments over a course of up to 65 individual sessions of ST. Focusing on repeated assessments within-individuals, we used mixed regression to test whether change in core-beliefs and therapeutic alliance preceded, followed, or occurred concurrently with change in depressive symptoms. Results: Changes in core-beliefs did not precede but were concurrently related to changes in symptoms. Repeated goal and task agreement ratings (specific aspects of alliance) of the same session, completed on separate days, were at least in part associated with concurrent changes in symptoms. Limitations: By design this study had a small sample-size and no control group. Conclusions: Contrary to what would be expected based on theory, our findings suggest that change in core-beliefs does not precede change in symptoms. Instead, change in these variables occurs concurrently. Moreover, alliance ratings seem to be at least in part colored by changes in current mood state. Highlights: The mechanisms that contribute to symptom change in psychotherapy are unknown. We tested schemas and working alliance as potential mechanisms of symptom change. Change in schemas/alliance did not predict subsequent symptom changes. Schemas and symptoms changed concurrently. Alliance ratings were related to concurrent mood changes.